Investigation of Dynamic Load in Superdeep Mine Hoisting Systems Induced by Drum Winding - Jiannan Yao (Hindawi Limited, 2021)
Blair mine hoists powered by drum winding are a key equipment in the transportation of a superdeep mine shaft. The step changes of hoisting velocity and acceleration caused by coil and layer crossover of rope winding on the LeBus drum, which will excite impact responses of hoisting systems, cannot be ignored in the hoisting system with high velocity. The paper focuses on investigating the effect of drum winding on impact responses of superdeep mine hoisting systems. Firstly, the hoisting velocity and acceleration were precisely modelled and calculated according to the structure of rope groove of the LeBus drum; secondly, impact responses of the dynamic displacement and load were obtained by applying the established model; eventually, an experiment was performed, and then, the validity of the established model and the response mechanism was verified. The paper will provide good technical support for the design and optimization of the mine hoists in superdeep mine shafts.